Correlations of p53, SLC7A11, and CD3+/CD8+ T cells with pathological features and prognosis in endometrial carcinoma - Lv, Yuanjie; Zhou, Weiwei; Zhang, Jingyu; Feng, Jing; Xing, Rongge; Miao, Zhigang (Journal of Medical Biochemistry, 2025)
Objective: This study investigates the clinical significance of SLC7A11, p53, and CD3+/CD8+ T cells in endometrial carcinoma (EC). By evaluating their expression patterns and correlations with histopathological parameters and patient outcomes, we aim to develop a prognostic risk model integrating these biomarkers.Methods: We enrolled 134 EC patients (observation group) diagnosed between February 2023 and January 2024 and 128 concurrent healthy controls. Quantitative and qualitative assessments were conducted to measure SLC7A11, p53, and CD3+/CD8+ T cell levels. Diagnostic performance of individual and combined markers was analyzed using receiver operating characteristic (ROC) curves, while a logistic regression-based predictive model was developed. Associations of these biomarkers with EC histopathological features and 1-year survival outcomes were further evaluated.Results: Compared to controls, EC patients exhibited notable reductions in CD3+/CD8+ T-cell infiltration but elevations in SLC7A11 and p53 expression (P
Keywords: p53; SLC7A11; CD3 T cells; CD8 T cells; endometrial carcinoma; Diagnosis